Fuzzy multicriteria for determining reasonable adjustment in housing - Delgado Méndez, Luis; Del Moral Ávila, Consuelo; Del Moral Ávila, Maria José; Tapia García, Juan Miguel; Valverde Palacios, Ignacio; Valverde Espinosa, Ignacio (Technological and Economic Development of Economy, 2019)
Legislative initiatives regarding universal accessibility promote the elimination of architectural barriers. This is a positive measure as it aims to ensure equal rights and opportunities for disabled people, in accordance with the Convention on the Rights of Persons with Disabilities (United Nations, 2006). One of the challenges facing society today is the determination of reasonable accommodation, a concept that encompasses those necessary modifications and adjustments which do not impose a disproportionate burden. For this purpose, technical, economic and social aspects shall be taken into consideration, as required by legislation. This paper proposes reasonable accommodation in residential buildings, taking into account the different options for its attainment, by applying a multi-criteria analysis based on a wide range of objective indicators of three types: technical, social and economic. This proposal was one of the objectives of the R + D + i Project called “VIVable-From accessible housing to sustainable housing: The essence of reasonable accommodation”. From VIVable, the fuzzy multi-criteria assessment method for determining reasonable accommodation may be totally extrapolated to other uses. At the same time, the proposed method may also be extrapolated to other countries where basic requirements for universal accessibility in buildings and equal rights of persons with disabilities are standardized. First published online 20 March 2019